Integrasi Augmented Reality Berbasis Budaya Lokal dalam Pemasaran UMKM untuk Keunggulan Kompetitif - Annisa Mardatillah; Sri Yuliani; Lilis Marina Angraini; Yusnidar Yusnidar (SYNERGY: Jurnal Bisnis dan Manajemen, 2026)
In order to better understand how culture-based augmented reality (AR) helps MSMEs in the creative sector boost their competitive edge, this study looks into the topic. Prior research has mostly focused on augmented reality (AR) as a promotional or technological tool, but little focus has been placed on how AR might be used to strategically activate local cultural values. This study uses a qualitative methodology to fill this gap by applying NVivo-assisted thematic analysis to the analysis of observational and in-depth interview data. According to the results, culture-based augmented reality serves as a fundamental strategic tool that combines digital marketing strategy, user experience, product differentiation, and cultural authenticity. By converting cultural histories, symbols, and identities into immersive digital interactions, augmented reality (AR) improves experience value and increases emotional customer engagement and perceived product value. The findings also show that by enhancing exposure, interaction, and shareability, AR-based cultural content promotes the spread of innovation via social media. Furthermore, it becomes clear that dynamic capacities and technology literacy are essential enabling aspects for MSMEs to use AR sustainably. This study theoretically expands on the Resource-Based View by showing how immersive digital technology might transform local culture into a unique and valuable resource. From a practical standpoint, the results indicate that incorporating AR with cultural values can help MSME competitiveness in the digital economy. It is recommended that future studies employ mixed-methods or quantitative methodologies to validate the suggested conceptual model in larger cultural contexts